2021
DOI: 10.1111/iwj.13708
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life and chronic wound characteristics among patients with chronic wounds treated in primary care: A cross‐sectional study in Singapore

Abstract: Chronic wounds commonly decrease patients' quality of life. Understanding how chronic wounds impact a patient's health‐related quality of life (HRQoL) is important for healthcare service delivery and treatment management. This study explored HRQoL among patients suffering from chronic wounds and investigated associations with patients' socio‐demographics and wound characteristics. Two hundred and thirty‐three patients across six primary care clinics were assessed and responded to a survey that collected inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 47 publications
(125 reference statements)
3
11
0
Order By: Relevance
“…In the present study, participants of Chinese ethnicity made up nearly two-thirds of the study population (62.9%) and less than one-third of the total study population were women (30.2%). The findings align with a recent study conducted in Singapore in a chronic wound population in primary care 21 . The mean wound area in the present study (7.8 ± 21.2 cm 2 ) was comparable to the findings of a recent study conducted in Singapore on patients with diabetic foot ulcer (7.0 ± 12.5 cm 2 ) 22 .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In the present study, participants of Chinese ethnicity made up nearly two-thirds of the study population (62.9%) and less than one-third of the total study population were women (30.2%). The findings align with a recent study conducted in Singapore in a chronic wound population in primary care 21 . The mean wound area in the present study (7.8 ± 21.2 cm 2 ) was comparable to the findings of a recent study conducted in Singapore on patients with diabetic foot ulcer (7.0 ± 12.5 cm 2 ) 22 .…”
Section: Discussionsupporting
confidence: 89%
“…The findings align with a recent study conducted in Singapore in a chronic wound population in primary care. 21 The mean wound area in the present study (7.8 ± 21.2 cm 2 ) was comparable to the findings of a recent study conducted in Singapore on patients with diabetic foot ulcer (7.0 ± 12.5 cm 2 ). 22 However, the mean age of the participants (27.9 ± 12.4 years) in the present study was much younger compared with the reported age of the patients with chronic wounds (61.2 ± 4.6 years) and diabetic foot ulcers (66.3 ± 11.3 years).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Globally, millions of people are affected by poor wound healing after major accidents, surgical complexities, burns, or associated chronic disease conditions, which, if not treated properly, even leads to patient mortality. Proper healthcare service delivery toward wound healing and its effective treatment management is thus very important, particularly for patients suffering from chronic or hard-to-heal wounds . Worldwide, almost 6.5 million people are affected, with chronic wounds imposing an unappreciated burden on them and the wound care society with wound care products amounting to almost $15 billion annually .…”
Section: Introductionmentioning
confidence: 99%